A lead BODIPY-phenylanthracene dyad for application in photodynamic therapy - Senge, Mathias; Callaghan, Susan; Filatov, Mikhail A.; Savoie, Huguette; Boyle, Ross W. (My University, 2019)
Over the past four years we have developed BODIPY dyads capable of triplet state generation from a charge transfer states generated by photoinduced electron transfer. In the current work we identify a lead compound for application in photodynamic therapy. This system is composed of a phenylanthracene electron donor unit and a dimethyl-substituted BODIPY acceptor unit. We have demonstrated that this compound, in submicromolar concentrations, can effectively generate singlet oxygen in polar solvents and induce cytotoxicity in human breast cancer cells (MDA-MB-468) when exposed to light. The photophysical properties of these compounds are chemically tunable and thus open the door not only to a new class of photodynamic therapy photosensitizers but also agents for triplet-triplet annihilation up-conversion applications
Keywords: BODIPY; Photodynamic therapy; Triplet state; Singlet oxygen; Photosensitizer